Photosynthetic Potential Of Foreign And Local Cotton Varieties Under Saline Soil Conditions (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
This article presents comprehensive data regarding the intensity of photosynthesis in local and foreign cotton varieties cultivated under soil salinity conditions. The study establishes the specific differences in the net photosynthetic productivity levels of the local Bukhara-8 variety in comparison with foreign genotypes, namely Xinluzao-57, Zongmian-88, Xinluzao-52, Zhongmian-113, Xinluzao-78, and Chjuntay-2, across both control and experimental variants. It was determined that the photosynthetic intensity of these cotton varieties is directly correlated with their salt tolerance characteristics, varying significantly depending on the specific variety, the experimental conditions, and the developmental stages of the plants. The findings highlight the physiological mechanisms of adaptation and the maintenance of metabolic efficiency in response to abiotic stress factors in diverse cotton germplasm
Keywords: cotton varieties; soil salinity; photosynthetic intensity